A cognitive-behavioral and mindfulness-based group sleep intervention improves behavior problems in at-risk adolescents by improving perceived sleep quality. (December 2017) - Blake, Matthew J.; Snoep, Lian; Raniti, Monika; Schwartz, Orli; Waloszek, Joanna M.; Simmons, Julian G.; Murray, Greg; Blake, Laura; Landau, Elizabeth R.; Dahl, Ronald E.; Bootzin, Richard; McMakin, Dana L.; et al.
Abstract: Objective: The aim of this study was to test whether a cognitive-behavioral and mindfulness-based group sleep intervention would improve behavior problems in at-risk adolescents, and whether these improvements were specifically related to improvements in sleep. Method: Secondary analysis of a randomized controlled trial conducted with 123 adolescent participants (female = 60%; mean age = 14.48, range 12.04–16.31 years) who had high levels of sleep problems and anxiety symptoms. Participants were randomized into either a sleep improvement intervention ( n  = 63) or an active control "study skills" intervention ( n  = 60). Participants completed sleep and behavior problems questionnaires, wore an actiwatch and completed a sleep diary for five school nights, both before and after the intervention. Results: Parallel multiple mediation models showed that postintervention improvements in social problems, attention problems, and aggressive behaviors were specifically mediated by moderate improvements in self-reported sleep quality on school nights, but were not mediated by moderate improvements in actigraphy-assessed sleep onset latency or sleep diary-measured sleep efficiency on school nights. Conclusion: This study provides evidence, using a methodologically rigorous design, that a cognitive-behavioral and mindfulness-based group sleep intervention improved behavior problems in at-risk adolescent by improving perceived sleep quality on school nights. These findings suggest that sleep interventions could be directed towards adolescents with behavior problems. Clinical Trial Registration: This study was part of The SENSE Study (Sleep and Education: learning New Skills Early). URL: ACTRN12612001177842;http://www.anzctr.org.au/TrialSearch.aspx?searchTxt=ACTRN12612001177842&isBasic=True . Highlights: We examined the effects of an adolescent sleep intervention on behavior problems. Improvements in behavior problems were mediated by improvements in perceived sleep quality. Sleep interventions could be directed towards adolescents with behavior problems.